Identifying characteristics of indicators of sedentary behavior using objective measurements. Issue 1 (10th October 2019) - Yamamoto, Kojiro; Matsuda, Fumiko; Matsukawa, Tsuyoshi; Yamamoto, Nao; Ishii, Kenji; Kurihara, Takahiro; Yamada, Shota; Matsuki, Taro; Kamijima, Michihiro; Ebara, Takeshi
Abstract: Objective: Recent attention has been focused on sedentary behavior (SB) affecting health outcomes, but the characteristics of indicators reflecting SB remain to be identified. This cross‐sectional study aims to identify the characteristics of indicators of SB, focusing on the examination of correlations, reliability, and validity of sedentary variables assessed by the smartphone app. Method: Objectively measured data of SB of eligible 46 Japanese workers obtained from smartphones were used. We assessed the characteristics of current indicators being used with a 10‐minute or 30‐minute thresholds, in addition to the conventional indicators of total sedentary time, mean sedentary bout duration, and total number of sedentary bouts. They were evaluated from three perspectives: (a) association among the indicators, (b) reliability of the indicators, and (c) criterion validity. Results: Total sedentary time under 10 minutes ( U10 ) and U30 had negative associations with Total sedentary time (r = −.47 and −.21 respectively). The correlation between Mean sedentary bout duration and Total number of sedentary bouts was −.84, whereas between Mean sedentary bout duration 10, 30 and Total number of sedentary bouts were −.54 and −.21, respectively. The intraclass correlation coefficients of almost all indicators were around .80. Mean sedentary bout duration, Mean sedentary bout duration 10, Total number of sedentary bouts, Total sedentary time 30, U30 and U10 have significant differences between three BMI groups. Conclusion: This study comprehensively revealed the rationale of advantage in the current indicator being used with a 10‐minute or 30‐minute threshold, rather than the conventional total amount of SB.